Cadaverine supplementation during a chronic exposure to difluoromethylornithine allows an overexpression, but prevents gene amplification, of ornithine decarboxylase in L1210 mouse leukaemia cells. - Alhonen-Hongisto, L (1987)
We recently selected a variant mouse L1210 leukaemia-cell line overproducing ornithine decarboxylase (ODC) (EC 4.1.1.17) as a result of chronic exposure to 2-difluoromethylornithine (DFMO) in the presence of micromolar concentrations of cadaverine. These cells, now grown for more than 2 years in the presence of DFMO and cadaverine, continued to accumulate ODC-specific mRNA in an amount 30-50 times higher than that in the parental cells, yet showing practically no changes in the gene dosage for the enzyme. However, analysis of the genomic DNA with the isoschizomeric restriction enzymes HpaII and MspI revealed that the ODC sequences in the overproducer cells were hypomethylated in comparison with the parental cells. The natural polyamines (putrescine, spermidine and spermine) were almost totally replaced by cadaverine and aminopropylcadaverine. Omission of cadaverine from the culture medium, but leaving 10 mM-DFMO, resulted in an about 10-fold ODC gene amplification within a few weeks. The accumulation of ODC mRNA was enhanced by the same factor. Concomitantly, the content of the natural polyamines was almost normalized, representing about 65% of that found in the parental cells. The present results suggest that, under a given selection pressure, an overproduction of the target gene product may be primarily based on an enhanced transcriptional activity, possibly associated with hypomethylation and, if not sufficient, a secondary amplification of the active gene occurs.